Inquisition vs. Art: Identification of an Image not Tolerated by the Spanish Holy Office in the 16th Century - Carretero Calvo, Rebeca (Eikón / Imago, 2023)
The detailed description of a painting prohibited by the Holy Office accused of incurring in Lutheran heresy contained in an agreement of the Council of the Spanish Inquisition in 1571 has made it possible to identify its representation through an engraving by Harmen Jansz. Muller (c. 1538-1617) entitled The Rich and the Poor before a Crucifix. Based on this, this article studies both the image of the censored painting from the inquisitorial document and the localized engraving, transcribing its inscriptions and analyzing its iconography. Likewise, the origin of the work is investigated, contextualizing it in the production of engravings in the Netherlands and in its tense relationship with the Spain of Philip II, dominated by the struggle against Protestantism. Finally, the reasons that could have led the inquisitors to purge this image are considered.